2007
DOI: 10.1261/rna.615508
|View full text |Cite
|
Sign up to set email alerts
|

Modulating alternative splicing by cotranscriptional cleavage of nascent intronic RNA

Abstract: Cotranscriptional cleavage mediated by a hammerhead ribozyme can affect alternative splicing if interposed between an exon and its intronic regulatory elements. This has been demonstrated using two different alternative splicing systems based on a-tropomyosin and fibronectin genes. We suggest that there is a requirement for intronic regulatory elements to be covalently attached to exons that are in turn tethered to the elongating polymerase. In the case of the alternatively spliced EDA exon of the fibronectin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…2A, top) a set of previously described simple (GT) and double (DM) mutations (Nogues et al 2003), or a deletion that eliminates an intronic downstream regulatory element (DDRE) ( Fig. 2B; Gromak et al 2008). All three mutations highly increase E33 inclusion levels by means of different mechanisms: GT and DM mutants strengthen the polypyrimidine tract (PPT) FIGURE 2.…”
Section: Different Cis-acting Mutations Enhance E33 Inclusion Throughmentioning
confidence: 99%
See 2 more Smart Citations
“…2A, top) a set of previously described simple (GT) and double (DM) mutations (Nogues et al 2003), or a deletion that eliminates an intronic downstream regulatory element (DDRE) ( Fig. 2B; Gromak et al 2008). All three mutations highly increase E33 inclusion levels by means of different mechanisms: GT and DM mutants strengthen the polypyrimidine tract (PPT) FIGURE 2.…”
Section: Different Cis-acting Mutations Enhance E33 Inclusion Throughmentioning
confidence: 99%
“…(A) Diagrams representing the two basic minigenes used in this study. (B) Mutations introduced in the minigenes shown in A. WT indicates wild-type sequence; GT and DM, G/T and G/T+A/T point mutations, respectively, at the polypyrimidine tract of the 39ss upstream of E33 (Nogues et al 2003); DDRE, deletion of the intronic downstream regulatory element (Gromak et al 2008). The minigenes containing two alternative splicing regions, WT (pFN-EDI WT /IIICS) and DM (pFN-EDI C /IIICS), were previously described (Fededa et al 2005).…”
Section: Different Cis-acting Mutations Enhance E33 Inclusion Throughmentioning
confidence: 99%
See 1 more Smart Citation
“…For the two genes, that cassette exon precedes the large intron carrying either the HH9 or HH10 ribozymes ( Figure 6 ). Although these observations offer just circumstantial support, previous experimental data obtained with intronic HHRs has revealed that certain intronic regulatory elements involved in processes of alternative splicing have to be covalently attached to exons, and the presence of intronic HHRs disrupt their usual behavior during splicing (Gromak et al , 2008 ;Pastor et al , 2011 ).…”
Section: Intronic Ribozymes Snrnas and Pre-mrna Splicingmentioning
confidence: 92%
“…15 This coupling of premRNA splicing and Pol II transcription brings another layer of regulation. [16][17][18][19][20] The C-terminal domain of Pol ll is necessary for proper pre-mRNA processing [21][22][23][24] and there are several lines of evidence indicating Pol II elongation rate affects splice site choice. [25][26][27][28][29] The fact that most introns are removed co-transcriptionally means splicing occurs while pre-mRNA is close to chromatin, which may further influence splicing decisions.…”
Section: Introductionmentioning
confidence: 99%